EFEKTIFITAS PROGRAM PEMBIAYAAN PAKET MASA DEPAN DI BTPN SYARIAH DALAM MEMBERDAYAKAN PEREMPUAN UNTUK MENGEMBANGKAN EKONOMI KELUARGA - AINUL IKHSAN; RAHMANI TIMORITA YULIANTI (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The theme of the research is: economics based on Islamic economics. The purpose of this study is to describe and analyze the effectiveness of financing products